OCTREOTIDE IN THE MANAGEMENT OF ENTEROCUTANEOUS FISTULAE - Mufti, Tariq S.; Akbar, Mohammad; Khan, Khalid (Journal of Ayub Medical College Abbottabad, 1995)
Efficacy of Octreotide (Somatostatin) in the conservative management of postoperative Enterocutaneous fistula was studied in seven patients with age ranging 1 to 70 years. Four out of seven fistulae closed within 21 days of starting the drug. One case, where fistula took over a month to close, responded well in reducing the output significantly within 10 days of starting therapy. The cases and the results are discussed. Favourable results following Octreotide therapy in this study need strengthening by further studies.